2022
DOI: 10.1177/23727322211068018
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Based Disparities in Youth Mental Health: Scope, Social Underpinnings, and Policy Implications

Abstract: Weight-based disparities in mental health impair the well-being of youth with overweight and obesity, who comprise a growing majority of young people in the United States. This review summarizes research regarding the extent of weight-based disparities in youth mental health and describes the social underpinnings of these disparities across contexts. Youth with high weight face frequent stigmatization (e.g., bullying, victimization, negative judgment), particularly in the school setting. Weight-based dispariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Accordingly, cisgender girls and transgender/gender diverse adolescents with BMIs in the 5th-85th percentiles may engage in more disordered eating behaviors than cisgender boys in the same BMI category (Romito et al, 2021). Cultivating more weight-inclusive (e.g., school wellness programs that emphasize health rather than weight) and genderinclusive school norms (e.g., using adolescents' chosen name and correct pronouns regardless of how a person's body conforms to gender expectations) may help mitigate these disparities (Lessard & Lawrence, 2022;Pollitt et al, 2021;Russell et al, 2018;Vantieghem & van Houtte, 2020) et al, 2015;Lessard & Lawrence, 2022;Saewyc et al, 2014) and establishing gender and sexuality alliances (Gower et al, 2020;Lessard et al, 2020) are two low-cost strategies found to reduce bias-based bullying, and may help mitigate disordered eating disparities among singly and multiply marginalized youth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, cisgender girls and transgender/gender diverse adolescents with BMIs in the 5th-85th percentiles may engage in more disordered eating behaviors than cisgender boys in the same BMI category (Romito et al, 2021). Cultivating more weight-inclusive (e.g., school wellness programs that emphasize health rather than weight) and genderinclusive school norms (e.g., using adolescents' chosen name and correct pronouns regardless of how a person's body conforms to gender expectations) may help mitigate these disparities (Lessard & Lawrence, 2022;Pollitt et al, 2021;Russell et al, 2018;Vantieghem & van Houtte, 2020) et al, 2015;Lessard & Lawrence, 2022;Saewyc et al, 2014) and establishing gender and sexuality alliances (Gower et al, 2020;Lessard et al, 2020) are two low-cost strategies found to reduce bias-based bullying, and may help mitigate disordered eating disparities among singly and multiply marginalized youth.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cisgender girls and transgender/gender diverse adolescents with BMIs in the 5th‐85th percentiles may engage in more disordered eating behaviors than cisgender boys in the same BMI category (Romito et al, 2021). Cultivating more weight‐inclusive (e.g., school wellness programs that emphasize health rather than weight) and gender‐inclusive school norms (e.g., using adolescents' chosen name and correct pronouns regardless of how a person's body conforms to gender expectations) may help mitigate these disparities (Lessard & Lawrence, 2022; Pollitt et al, 2021; Russell et al, 2018; Vantieghem & van Houtte, 2020). To illustrate, evidence suggests that some transgender/gender diverse adolescents engage in disordered eating behaviors to prevent or delay pubertal development and/or cope with gender‐related distress, gender dysphoria (Coelho et al, 2019; Roberts et al, 2021; Romito et al, 2021), but that body image and disordered eating may improve when their gender identity is affirmed consistently (Roberts et al, 2021; Testa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher weight not only carries risks of physical diseases, like cardiovascular disease and type 2 diabetes, but also affects current and future mental health . This issue is increasingly critical as the growing rates of overweight and obesity in adolescence often extend into early adulthood …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that being young, being female, living in a non-Western area, and having obesity are potential risk factors for developing depression or depressive symptoms [7]. However, other studies have not found a relationship between weight status and mental health [8,9]. Nevertheless, the few meta-analyses of longitudinal studies have revealed a bidirectional relationship between depression and obesity [10,11].…”
Section: Introductionmentioning
confidence: 99%